Information technology /Business basics - BPP. ([S.l.] : BPP Publishing Ltd, 1997)
From a range of study guides for business degree students combining a user-friendly style of a study guide with the detail of a textbook. It is a blend that reflects the changing university environment in which self-study is becoming increasingly important. This revised edition features the use of icons to signpost the student through the book, case examples to illustrate technical points, over 100 multiple-choice questions, and exam style questions.
Keywords: business basics,information technology